مسؤولية الإدارة عند التعسف في استخدام القوة أو الانحراف فيها: دراسة مقارنة - حمزة, وليد مرزة; حسين, حيدر علي (Journal of Legal Sciences, 2019)
Use management of the force to protect public order and not be entertained and permissible in all cases, but management must comply with the reasons and principles governing such use, so that does not count the use of force by members of the public authority Bamahzawr and then claimed materialize because of arbitrariness or deviation in the use of force, physical and moral, both. To achieve management responsibility for two can Aaoss traditional direction in which resides the responsibility on the wrong basis or without error, but the developments and the expansion of the use of force management activity in most cases to deal with the turmoil facing the country if possible carry this responsibility on the text of the law directly.Since the establishment of this responsibility is not limited to only the criminal liability that may take pictures overtaking Feith use of force or the use of an image of cruelty, but can be realized with civil liability in addition to the disciplinary responsibility for business management